Development of a Novel Adapter to Enable Less-Invasive Left Ventricular Assist Device Implantation via the Left Ventricular Apex. Issue 9 (13th April 2022) - Schibilsky, David; Scheumann, Johannes; Koester, Philipp Julian; Demir, Halil; Rausch, Manuel; Puiu, Paul; Benk, Christoph; Maier, Sven; Neudorf, Simon; Diel, Patric; Grundmann, Sebastian; Kaier, Klaus; et al.
Abstract : The first prototype of an adapter to enable left ventricular assist device (LVAD) implantation solely via the left ventricular (LV) apex and without requiring cardiopulmonary bypass (CPB) was tested in healthy and acutely failing pig hearts. The adapter consists of a fixation, blood guiding, and connecting module fitting to a HeartMate 3 (HM3; Abbott, Chicago, IL) pump. Implantation was performed via a left thoracotomy in five pigs (96 ± 18 kg). Invasive blood pressure was measured before (CTRL), 30 minutes after HM3 initiation (HM3_CTRL), during acute heart failure (HF) induced by rapid pacing (CTRL_HF), and 5 minutes after initiating HM3 support (HM3_HF). To further estimate the LVAD performance, blood pressure amplitudes were calculated in the healthy heart without (CTRL) and with HM3 support (HM3_CTRL) as: systolic–diastolic blood pressure. Our adapter implantation and connection to the HM3 pump succeeded in all animals. Compared to the normal beating healthy heart, blood pressure amplitudes were significantly smaller during HM3 support (CTRL: 41 ± 5 mm Hg vs. HM3_CTRL: 20 ± 4 mm Hg; p < 0.05). Under HF conditions, mean blood pressure returned to normal values after pump initiation (CTRL_HF: 29 ± 6 mm Hg, HM3_HF: 83 ± 24 mm Hg). The adapter prototype allowed safe, straightforward, and less-invasive LVAD implantation solely via the LV apex without using CPB and support of the LV during acute HF in the pig heart.